Evaluating the association of common PBX1 variants with type 2 diabetes - Hercberg Serge; Tichet Jean; Marre Michel; Charpentier Guillaume; Duesing Konsta; Balkau Beverley; Froguel Philippe; Gibson Fernando (BMC, 2008)
Abstract Background PBX1 is a biological candidate gene for type 2 diabetes at the 1q21-q24 susceptibility locus. The aim of this study was to evaluate the association of common PBX1 variants with type 2 diabetes in French Caucasian subjects. Methods Employing a case-control design, we genotyped 39 SNPs spanning the PBX1 locus in 3,093 subjects to test for association with type 2 diabetes. Results Several PBX1 SNPs, including the G21S coding SNP rs2275558, were nominally associated with type 2 diabetes but the strongest result was obtained with the intron 2 SNP rs2792248 (P = 0.004, OR 1.20 [95% CI 1.06-1.37]). The SNPSpD multiple testing correction method gave a significance threshold of P = 0.002 for the 39 SNPs genotyped, indicating that the rs2792248 association did not survive multiple testing adjustment. SNP rs2792248 did not show evidence of association with the French 1q linkage signal (P = 0.31; weighted NPL score 2.16). None of the PBX1 SNPs nominally associated with type 2 diabetes were associated with a range of quantitative metabolic traits in the normoglycemic control subjects Conclusion The available data does not support a major influence of common PBX1 variants on type 2 diabetes susceptibility or quantitative metabolic traits. In order to make progress in identifying the elusive susceptibility variants in the 1q region it will be necessary to carry out further large association studies, meta-analyses of existing data from individual studies, and deep resequencing of the 1q region.